ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, CASH RATIOI, DEBT TO EQUITY RATIO DAN GROWTH OPPORTUNITY TERHADAP KEBIJAKAN DIVIDEN - Citra Ayu Wulandari; Reni Oktavia; Farichah Farichah; Ninuk Dewi Kusumaningrum (Jurnal Akuntansi dan Keuangan (JAK), 2020)
The research aims to examine the effect of managerial ownership, cash ratio, debt to equity ratio, and growth opportunity on dividend policy. The sample in this study was selected using purposive sampling and obtained 150 samples of companies listed on the Indonesia Stock Exchange in 2013-2018 that met the criteria. The results of hypothesis testing with multiple linear regression analysis using the SPSS 25 application show that managerial ownership, cash ratio, debt to equity ratio, and growth opportunity simultaneously have a significant effect on dividend policy. Partially, managerial ownership has a positive but not significant effect on dividend policy and cash ratio has a significant effect with a positive coefficient on dividend policy. While the debt to equity ratio, and growth opportunity have a significant effect with a negative coefficient on dividend policy.